2017
DOI: 10.1105/tpc.17.00830
|View full text |Cite
|
Sign up to set email alerts
|

MLK1 and MLK2 Coordinate RGA and CCA1 Activity to Regulate Hypocotyl Elongation inArabidopsis thaliana 

Abstract: Gibberellins (GAs) modulate diverse developmental processes throughout the plant life cycle. However, the interaction between GAs and the circadian rhythm remains unclear. Here, we report that MUT9p-LIKE KINASE1 (MLK1) and MLK2 mediate the interaction between GAs and the circadian clock to regulate hypocotyl elongation in Arabidopsis thaliana. DELLA proteins function as master growth repressors that integrate phytohormone signaling and environmental pathways in plant development. MLK1 and MLK2 interact with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 61 publications
4
37
0
Order By: Relevance
“…The transcription factor SUF4 interacts with MOS1 (MODIFIER OF snc1) to regulate the flowering time (Li et al ., 2010; Bao et al ., 2014). Recent results have supported the idea that transcriptional factors are critical for histone phosphorylation to regulate flowering time and hypocotyl elongation in Arabidopsis (Su et al ., 2017; Zheng & Ding, 2018; Zheng et al ., 2018). …”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor SUF4 interacts with MOS1 (MODIFIER OF snc1) to regulate the flowering time (Li et al ., 2010; Bao et al ., 2014). Recent results have supported the idea that transcriptional factors are critical for histone phosphorylation to regulate flowering time and hypocotyl elongation in Arabidopsis (Su et al ., 2017; Zheng & Ding, 2018; Zheng et al ., 2018). …”
Section: Discussionmentioning
confidence: 99%
“…The reduced transcript levels and H3K4me3 levels, at specific GA‐pathway genes, might require a specific transcription factor, which would trigger the targeting of SDG721 and SDG705 to these genes. Recent studies suggested that histone phosphorylation involved in flowering time and hypocotyl elongation is dependent on a transcriptional factor (Su et al ; Zheng et al ). SDG721 and SDG705 are closely related to ATX3, ATX4, and ATX5, suggesting that SDG721 and SDG705 might be involved in anther development.…”
mentioning
confidence: 99%
“…We quantified the concentration of GAs and found that the major bioactive gibberellin GA 4 was elevated in cry1 cry2 and phot1 phot2 cry1 cry2 , in accordance with the previous hypothesis that CRY protein negatively regulate the cellular level of GAs (Zhao et al ; Tsuchida‐Mayama et al ). However, no significant difference was found for the GA 4 level in phot1 phot2 mutants on medium with and without sucrose (Figure A), indicating that the effect of depleting sucrose on restoration of phototropism was not related to GA. As demonstrated by previous study, GAs and sucrose control the balance of DELLAs (Li et al ), which negatively regulate hypocotyl growth (Zhao et al ; Zheng et al ), and this mediations appear to play a positive role in hypocotyl gravitropism in Arabidopsis . However, the function of the DELLA proteins in hypocotyl phototropism is not known.…”
Section: Discussionmentioning
confidence: 62%